Genome re‐sequencing and simple sequence repeat markers reveal the existence of divergent lineages in the Canadian Puccinia striiformis f. sp. tritici population with extensive DNA methylation. (25th March 2018) - Brar, Gurcharn S.; Ali, Sajid; Qutob, Dinah; Ambrose, Stephen; Lou, Kun; Maclachlan, Ron; Pozniak, Curtis J.; Fu, Yong‐Bi; Sharpe, Andrew G.; Kutcher, Hadley R.
Summary: Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is an important disease in Canada. The worldwide genetic structure of Pst populations have been characterized, excluding Canada. Here, we elucidated the genetic structure of the western Canadian Pst population using molecular markers, revealing the presence of four divergent lineages with predominantly clonal structure. In the worldwide context, two previously reported lineages were identified: PstS0 (22%), representing an old Northwestern‐European and PstS1 (35%), an invasive warm‐temperature adapted. Additionally, two new, unreported lineages, PstPr (9%) and PstS1 ‐related (35%), were detected, which produced more telia than other lineages and had double the number of unique recombination events. The PstPr was a recent invasion, and likely evolved in a diverse, recombinant population as it was closely related to the PstS5, PstS7 /Warrior, PstS8 /Kranich, and PstS9 lineages originating from sexually recombining populations in the centre of diversity. The DNA methylation analysis revealed DNA‐methyltransferase1‐homologs, providing compelling evidence for epigenetic regulation and as a first report, an average of ∼5%, 5hmC in the Puccinia epigenome merits further investigation. The divergent lineages in the Canadian Pst population with the potential for genetic recombination, as well as epigenetic regulation needs consideration in the context of pathogen adaptation and management.